2014
DOI: 10.3389/fnbeh.2014.00136
|View full text |Cite
|
Sign up to set email alerts
|

Learning and memory impairments in a neuroendocrine mouse model of anxiety/depression

Abstract: Cognitive disturbances are often reported as serious incapacitating symptoms by patients suffering from major depressive disorders (MDDs). Such deficits have been observed in various animal models based on environmental stress. Here, we performed a complete characterization of cognitive functions in a neuroendocrine mouse model of depression based on a chronic (4 weeks) corticosterone administration (CORT). Cognitive performances were assessed using behavioral tests measuring episodic (novel object recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 70 publications
12
88
0
2
Order By: Relevance
“…Many studies have reported that elevated corticosterone concentrations contributed to stress-induced impairments in cognitive and learning abilities [8]. In our study, the serum corticosterone level was markedly increased after noise exposure, while treatment with orientin markedly decreased the serum corticosterone level.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Many studies have reported that elevated corticosterone concentrations contributed to stress-induced impairments in cognitive and learning abilities [8]. In our study, the serum corticosterone level was markedly increased after noise exposure, while treatment with orientin markedly decreased the serum corticosterone level.…”
Section: Discussionsupporting
confidence: 55%
“…In a continuously open auditory system, noise-induced stress can cause the significant release of hypothalamic hormones such as the corticotrophin-releasing hormone and the adrenocorticotropic hormone, which increase the activity of the HPA-axis and the release of corticosterone from the adrenal cortex [7]. It is known that high levels of corticosterone, induced by the hyperactivity of the HPA axis, impair cognition, including learning, memory, and spatial recognition [8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the hippocampus is a main structure for spatial learning and memory and, together with the amygdala and prefrontal cortex [22] and is susceptible to stress and senescence when glucocorticoid injury produces dendritic remodeling of CA3 pyramidal neurons and a decrement in adult neurogenesis in the dentate gyrus [23]. Moreover, these alterations are related also to emotional response impairments [21] and stress represents also the major precipitating factor in mood disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies in late-life depression have demonstrated a reduction in hippocampal volume in the depressed elderly population [167][168]. Studies with animal models have also shown that these structural abnormalities in the hippocampus or cortex are associated with cognitive deficits in memory and decision-making, as well as depression [169][170][171].…”
Section: Accepted Manuscriptmentioning
confidence: 97%